Analysis on emotional intelligence levels of physical education and sports students in sports - Yücel, Ali Serdar; Özdayi, Nahit (Horizon Research Publishing, 2019)
The purpose of this descriptive study is to compare the emotional intelligence levels and demographic attributes of students enrolled in different departments of Balıkesir University School of Physical Education and Sports during the 2018-2019 academic year. The research population was composed of 865 students receiving education in different departments of School of Physical Education and Sports, while the sample is composed of randomly selected 304 students among this population. The study utilized “Emotional Intelligence Inventory in Sports” developed by Schutte et al. (1998), revised and adapted by Lane et al. (2009) for use in sports with Turkish reliability and validity performed by Adiloğulları and Görgülü (2015). ?=0.927 was established as the reliability coefficient of the inventory. The Anova test, Kruskal Wallis test and Jonckheere-Terpstra test were used in data analysis. All analyses were performed with SPSS v17.0 (SPSS Science, Chicago, IL, USA). The study concluded emotional intelligence levels of the participants differ in the variable of age in the dimensions of using feelings, in the variable of department in the dimensions of evaluating one’s own feelings and social skills, and finally a difference existed in the variable of age concerning life satisfaction. Moreover, no relation was ascertained between the emotional intelligence of the participants and their life satisfaction. © 2019 by authors, All rights reserved.
Keywords: Emotional intelligence; Sports; Student